IMPLEMENTING THE EUROPEAN LANGUAGE PORTFOLIO (ELP) TO ENHANCE STUDENTS’ ABILITY IN WRITING NARRATIVE TEXT - Nursamsu, Nursamsu (Pusat Pengembangan Bahasa IAIN Tulungagung, 2014)
One of the text types to be taught to junior high school is a narrative text. It is a short story that is used to inform or entertain the readers or listeners (Anderson &Anderson, 1997). Anyhow, many students at State Junior High School of Kedungwaru 3 Tulungagung face problems in writing this kind of text. Before conducting the study, the researcher carried out a preliminary study to know the practical problems faced by the students. The result of the preliminary study showed that almost all students get difficulties to find a topic and develop it into a narrative text. Therefore, this study is aimed at providing a good strategy for students to write a good narrative text. This action research involved 30 students of the eighth grade and was conducted in two cycles. Each cycle consists of two meetings. The strategy was implemented by following the four steps of action research: planning, implementing, and observing the action, followed by reflection. The results of the findings showed that the teaching of narrative text by using the European Language Portfolio could enhance the students? ability in writing. More specifically, it was found out that many of the students could produce ?sufficient? to ?excellent? narrative text assessed with the writing rubric adapted from the Behrman (2003:297). Due to the success of the implementation of the European Language Portfolio, teachers of English are suggested to consider implementing the strategy to help students write narrative texts.